The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/acn3.51175
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of homozygous FIG4‐p.Ile41Thr Charcot‐Marie‐Tooth 4J patients

Abstract: We describe the clinical, electrodiagnostic, and genetic findings of three homozygous FIG4‐c.122T>C patients suffering from Charcot‐Marie‐Tooth disease type 4J (AR‐CMT‐FIG4). This syndrome usually involves compound heterozygosity associating FIG4‐c.122T>C, a hypomorphic allele coding an unstable FIG4‐p.Ile41Thr protein, and a null allele. While the compound heterozygous patients presenting with early onset usually show rapid progression, the homozygous patients described here show the signs of relative clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Defects in the PIKfyve complex are linked to human diseases, especially those of the nervous system [ 32 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], although the underlying molecular mechanisms are not clear. For example, mutations in Fig4 predicted to have a modest effect in the regulation of PI(3,5) 2 are linked to Charcot-Marie-Tooth syndrome (CMT4J), a peripheral neuropathy, as well as some cases of amyotrophic lateral sclerosis (ALS) and primary lateral sclerosis (PLS).…”
Section: Introductionmentioning
confidence: 99%
“…Defects in the PIKfyve complex are linked to human diseases, especially those of the nervous system [ 32 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], although the underlying molecular mechanisms are not clear. For example, mutations in Fig4 predicted to have a modest effect in the regulation of PI(3,5) 2 are linked to Charcot-Marie-Tooth syndrome (CMT4J), a peripheral neuropathy, as well as some cases of amyotrophic lateral sclerosis (ALS) and primary lateral sclerosis (PLS).…”
Section: Introductionmentioning
confidence: 99%
“…In this family, the patient’s father is of Northern European descent and likely carries this ancestral mutation originating in Europe. It has been reported that compound heterozygotes with this mutation diagnosed with CMT4J usually show early onset with rapid progression [ 9 ]. In contrast, our patient demonstrates that even in those carrying this mutation, the onset can be late and progression slow.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty CMT4J cases with homozygous or compound heterozygous FIG4 variants that were involved with CNS anomalies have been reported (Table 2). The p.I41T variant was a recurrent mutation reported in a number of unrelated families (11). It has been estimated that the population frequency of this allele was 0.001 (1).…”
Section: Literature Reviewmentioning
confidence: 99%